Pengaruh Transformational Leadership, Green Human Resources Management Terhadap Business Sustainability Dimediasi Innovation Organizational Pada Karyawan Generasi Milenial Cafe Atau Restoran Tiara Cibarusah Wilayah Kabupaten Bekasi - Della Rizki Fhadhilah; Retno Purwani Setyaningrum (Peneliti.net, 2023)
Indonesian businessment must pay close attention to any problems that exist in the business sector. This study aims to measure the influence of Transformational leadership, Green Human Resources Management on Business Sustainability mediated by Organizational Innovation in millennial generation employees at the Tiara Cibarusah cafe or restaurant in the Bekasi Regency area. This data was analyzed using quantitative methods, saturated sampling techniques with a sample of 41 respondents. The processing of this research applies the SmartPLS 3.0 software program. The results of the analysis in this study found that there was a significant influence between Transformational Leadership on Business Sustainability of millennial generation employees at the Tiara Cibarusah cafe or restaurant in the Bekasi Regency area. There is a significant influence of Transformational Leadership on Organizational Innovation for millennial generation employees at the Tiara Cibarusah cafe or restaurant in the Bekasi Regency area. There is a significant influence of Organizational Innovation on Business Sustainability of millennial generation employees of the Tiara Cibarusah café or restaurant in the Bekasi Regency area. There is a significant influence of Transformational Leadership on Business Sustainability through Organizational Innovation of millennial generation employees at the Tiara Cibarusah cafe or restaurant in the Bekasi Regency area. There is a significant influence of Green Human Resources Management on Business Sustainability.